The world of β-glucans : a review of biological roles, applications and potential areas of research - Ali, Syed Haris (University of Tromsø, 2009)
Among many known and tested immunomodulators, polysaccharides isolated from various natural sources occupy a prominent position. An important group of these polysaccharides is represented by the homopolymers of β-glucose, called β-glucans. Their very low-to-negligible toxicity and immunomodulating effects show the promise it has in the therapy of a variety of infectious and cancer illnesses. Nowadays, the popularity of Glucans as food additive and a disease-modifying agent is increasing. Here, a review of the various biological roles, applications and potential areas of β-glucan research is presented. Also, a short introduction to current work by the Glucan group in Tromsø is provided. The goal has remained to understand and aptly present the diverse roles of β-glucans and pin-pointing the prospective areas of research, both on the receptor / biochemical level, and in clinical research. It seems that with the tide of modern medical research, gradually, β-glucans will take the position they deserve in diagnostic and preventive medicine.